Preparation method and application of graphite negative electrode material containing dicarboxylic acid MOFs

CN122889716APending Publication Date: 2026-10-09FUJIAN SHANSHAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610956399.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

已有研究尝试将MOFs衍生物与石墨复合以提升性能,现有技术中采用MOFs前驱体经热处理制备多孔石墨材料,但该方法主要侧重物理结构调控,未能充分利用MOFs中羧酸基团所构建的化学活性界面,导致离子吸附与传导能力提升有限,容量优势并不显著

Benefits of technology

本申请采用4,4’-二苯乙烯二羧酸作为有机配体,其羧酸基团(-COOH)中的氧原子能与锆(Zr)等高价金属离子形成强大的配位键,构筑出热稳定性和化学稳定性极高的MOFs框架,这保证了后续高温碳化过程后能够衍生出结构稳固的多孔碳、金属氧化物复合物;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889716A_ABST
    Figure CN122889716A_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of a graphite negative electrode material containing dicarboxylic acid MOFs, which comprises the following steps: S1, mixing an organic ligand, a zirconium salt and a solvent, and performing a reaction by increasing the temperature to obtain a reaction product; S2, filtering the reaction product after cooling, washing the filter residue, and then performing suction filtration and drying to obtain a carboxylic acid MOF; S3, dispersing the carboxylic acid MOF and graphene oxide into anhydrous ethanol, and adding a phenolic resin to obtain a mixture; S4, drying the mixture to remove the solvent, and then performing temperature solidification to obtain a pre-solidified product; S5, performing high-temperature carbonization treatment under the condition of an inert gas to obtain a carbonization product; and S6, immersing the obtained carbonization product in a hydrogen fluoride solution to remove inorganic impurities, then washing to neutral, and drying to obtain a graphite negative electrode material containing dicarboxylic acid; the organic ligand in the step S1 contains at least two carboxylic acid groups. The application has the effect of improving the capacity and stability of an electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery anode materials, and in particular to a method for preparing and applying a graphite anode material containing dicarboxylic acid MOFs. Background Technology

[0002] With the rapid development of new energy vehicles and large-scale energy storage industries, the market has placed higher demands on the energy density, fast-charging performance, and cycle life of lithium-ion batteries. As a key component of batteries, the performance optimization of anode materials is crucial. Currently, commercial graphite anodes are widely used due to their low cost, stable potential, and stable cycling performance. However, their relatively low theoretical specific capacity and slow ion diffusion rate limit further improvements in battery performance, especially under rapid charge and discharge conditions, where they are prone to capacity decay and increased polarization.

[0003] In recent years, metal-organic frameworks (MOFs) have shown great potential in the field of electrochemical energy storage due to their high specific surface area, tunable pore structure, and abundant surface functional groups. Among them, MOFs containing carboxylic acid groups can form stable porous frameworks through strong coordination and provide a large number of active sites conducive to lithium-ion adsorption and transport, offering new ideas for the design of anode materials. Existing studies have attempted to combine MOF derivatives with graphite to improve performance. Current techniques use MOF precursors to prepare porous graphite materials through heat treatment, but this method mainly focuses on physical structure regulation and fails to fully utilize the chemically active interfaces constructed by the carboxylic acid groups in MOFs, resulting in limited improvement in ion adsorption and conduction capabilities and no significant capacity advantage. Summary of the Invention

[0004] To further improve the capacity and stability of electrode materials, this application provides a method for preparing and applying a graphite anode material containing dicarboxylic acid MOFs.

[0005] In the first aspect, this application provides a graphite anode material containing dicarboxylic acid MOFs, which adopts the following technical solution: A graphite anode material containing dicarboxylic acid MOFs includes the following steps: S1. Mix the organic ligand, zirconium salt and solvent, and heat to react to obtain the reactants; S2. After cooling the reactants, filter them, remove the filter residue, wash it, then filter and dry it to obtain carboxylic acid MOFs; S3. Disperse carboxylic acid MOFs and graphene oxide in anhydrous ethanol, add phenolic resin, and obtain a mixture; S4. Dry the mixture to remove the solvent, then heat it to cure, and obtain the pre-cured product; S5. High-temperature carbonization under inert gas conditions yields carbonized products; S6. The obtained carbonized product is soaked in hydrogen fluoride solution to remove inorganic impurities, then washed until neutral, and dried to obtain graphite anode material containing dicarboxylic acid. In step S1, the organic ligand contains at least two carboxylic acid groups.

[0006] By adopting the above technical solution, a complete path from material synthesis to the final composite anode material was constructed. First, MOFs containing dicarboxylic acids were synthesized by solvothermal method. The abundant and stable carboxylic acid groups provided potential active sites for subsequent lithium-ion transport. The MOFs were uniformly mixed with graphene oxide and phenolic resin in a solvent to lay the foundation for the formation of a composite structure. Then, through curing and high-temperature carbonization processes, the phenolic resin was transformed into a continuous amorphous carbon skeleton, and the porous carbon derived from MOFs was bonded to the graphene oxide network. Simultaneously, the carbonization of each component and partial reduction of graphene were completed. Finally, the material was treated with hydrofluoric acid solution to remove impurities and further purify more electrochemical active surfaces. The prepared graphite anode material containing dicarboxylic acids has high-capacity active material, contains conductive agents and binder phases, and the components have good interfacial compatibility and structural stability.

[0007] Preferably, the organic ligand in step S1 is 4,4'-stilbene dicarboxylic acid, and the zirconium salt is preferably zirconium tetrachloride.

[0008] By adopting the above technical solution, a specific MOF constructed with 4,4'-stilbene dicarboxylic acid and zirconium tetrachloride has a rigid conjugated structure and two carboxyl groups, which can form stable zirconium-oxygen cluster nodes with zirconium ions. After subsequent high-temperature carbonization, it can maintain high stability of the porous carbon framework structure, which is beneficial to inheriting the advantages of high specific surface area and regular pores of MOFs. Furthermore, the rigid structure helps to suppress structural collapse during the carbonization process, providing a stable and abundant transport channel for lithium ions.

[0009] Preferably, the mass ratio of 4,4'-stilbene dicarboxylic acid to zirconium tetrachloride is 1:(0.7-0.8). By adopting the above technical solution, and preferably within the above range the mass ratio of 4,4'-stilbene dicarboxylic acid to zirconium tetroxide, the coordination reaction between the carboxylic acid groups and zirconium ions in the reaction system tends to be more complete, which promotes the formation of MOFs materials with complete well structure and controllable defects, and further improves the stability of the prepared graphite anode material.

[0010] Preferably, in step S1, the temperature for the reaction between the organic ligand and the zirconium salt is 110-130℃, and the reaction time is 22-24h.

[0011] By adopting the above technical solution, and preferably within the above range of reaction temperature and reaction time, the prepared MOFs crystals have uniform particle size and high crystallinity, which makes the graphite anode material prepared subsequently have good stability.

[0012] Preferably, in step S2, the drying temperature of the filter residue after washing and filtration is 110-130℃, and the drying time is 6-12h.

[0013] By adopting the above technical solution, and preferably within the range of drying temperature and drying time, solvent molecules inside and on the surface of MOFs can be effectively removed, and the decomposition and collapse of the MOFs framework structure caused by excessive temperature can be reduced, thereby improving the stability of the system.

[0014] Preferably, in step S3, the mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol is 1:(0.8-1.2):1:20.

[0015] By adopting the above technical solution, MOF-derived carbon provides capacity as the main active lithium storage sites; limiting graphene oxide to the above range is sufficient to construct a continuously encapsulated two-dimensional ultrafast electronic conduction network; an equal amount of phenolic resin can ensure the formation of a continuous carbon binder phase that fully encapsulates and connects all components, and an appropriate amount of solvent ensures uniform dispersion.

[0016] Preferably, in step S3, the phenolic resin is a first-order phenolic resin.

[0017] By adopting the above technical solution, the active hydroxymethyl groups abundant in the molecular chain of the methyl phenolic resin can chemically react with the incompletely coordinated carboxylic acid groups on the surface of MOFs and the oxygen-containing functional groups at the edge of graphene oxide during the heating and curing stage, forming strong chemical bonds and significantly enhancing the interfacial bonding force. During the carbonization stage, its self-crosslinking characteristics produce a continuous amorphous carbon phase with high carbon yield, firmly connecting the MOFs-derived carbon and the graphene oxide network into a whole, greatly improving the structural stability of the composite electrode material during long-term cycling.

[0018] Preferably, in step S5, the high-temperature carbonization temperature is 880-920℃ and the carbonization time is 5-8h.

[0019] By adopting the above technical solution, at the above carbonization temperature, phenolic resin is fully carbonized into amorphous carbon with good conductivity, and the effective thermal reduction of graphene oxide is promoted to restore its high conductivity.

[0020] Secondly, this application provides an application of a graphite anode material containing dicarboxylic acid MOFs, employing the following technical solution: Application of a graphite anode material containing dicarboxylic acid MOFs, wherein the graphite anode material containing dicarboxylic acid MOFs is used in lithium-ion batteries.

[0021] In summary, this application includes at least one of the following beneficial technical effects: This application uses 4,4'-stilbene dicarboxylic acid as an organic ligand. The oxygen atom in its carboxylic acid group (-COOH) can form strong coordination bonds with high-valence metal ions such as zirconium (Zr), constructing a MOF framework with extremely high thermal and chemical stability. This ensures that a structurally stable porous carbon-metal oxide composite can be derived after the subsequent high-temperature carbonization process. This application uses a methyl phenolic resin, which contains a large amount of hydroxymethyl (-CH2OH) in the prepolymer. During the drying process at 60℃ and curing at 200℃, the carboxyl groups (-COOH) on the surface of MOFs and the hydroxymethyl groups (-CH2OH) of the resin may undergo esterification condensation reaction (forming -COOCH2-), or generate strong interaction through hydrogen bonds. This means that it is not a simple physical encapsulation. After carbonization, this bond will be transformed into a strong chemical connection between MOFs derivatives and continuous carbon skeleton, which greatly enhances the interfacial bonding force and solves the common problems of high interfacial resistance and easy detachment of composite materials. This application utilizes the rich and tunable hierarchical channels and surface active sites of MOF-derived carbon to greatly expand the storage space and reaction interface of lithium ions. At the same time, by using the two-dimensional conductive sheets of graphene oxide and the three-dimensional continuous carbon skeleton formed by phenolic resin curing and carbonization, a three-dimensional conductive network from micro to macro is constructed. This strong interfacial bonding and three-dimensional interconnected conductive pathway shortens the diffusion path of lithium ions and reduces the charge transfer impedance, thereby significantly improving the reversible capacity, rate performance and cycle stability of lithium battery anode materials. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the material structure in this application.

[0023] Figure 2 This is a comparative diagram of the electrochemical performance of Examples 1-4 and Comparative Examples 1-2 of this application.

[0024] Figure 3 These are the rate performance diagrams of Examples 1-4 and Comparative Examples 1-2 of this application. Detailed Implementation

[0025] All raw materials are available commercially; Example 1

[0026] Preparation of graphite anode materials containing dicarboxylic acid MOFs: S1. Weigh 1.16g of 4,4'-stilbene dicarboxylic acid and 0.85g of zirconium tetrachloride and add them to the reaction vessel. Then add 200ml of anhydrous N,N-dimethylformamide solvent, sonicate for 15min to mix thoroughly, and then react in an oven at 120℃ for 24h to obtain the reactant. S2. After the reactor is cooled, the suspension is filtered, the filter residue is removed, and washed three times each with N,N-dimethylformamide and petroleum ether. Then, it is filtered and dried in a vacuum oven at 120°C for 6 hours to obtain yellowish-white crystals, namely carboxylic acid MOFs. S3. Disperse the carboxylic acid MOF particles and the ground graphene oxide evenly in anhydrous ethanol solvent, and then add methyl phenolic resin. The mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol is 1:1:1:20. Stir and mix to make the components evenly mixed to obtain a mixture. S4. Dry the mixture in a 60°C oven for 2 hours to remove the solvent, and then cure it at 200°C for 2 hours to crosslink and cure the phenolic resin, thus obtaining a pre-cured product. S5. Carbonize at 900℃ under inert gas conditions for 5 hours with a heating rate of 2℃ / min. The carbonized product is obtained after carbonization. S6. The obtained carbonized product is soaked in 6% HF solution for 12 hours to remove inorganic impurities. Then it is washed with deionized water until neutral and dried in an oven at 60°C for 12 hours to obtain a graphite anode material containing dicarboxylic acid. Example 2

[0027] Example 2 is based on Example 1. The difference between Example 2 and Example 1 is that the mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol in step S3 of Example 2 is 1:0.5:1:20. Example 3

[0028] Example 3 is based on Example 1. The difference between Example 3 and Example 1 is that the mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol in step S3 of Example 3 is 1:1:0.5:20. Example 4

[0029] Example 4 is based on Example 1. The difference between Example 4 and Example 1 is that the mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol in step S3 of Example 4 is 1:1:2:20.

[0030] Comparative Example 1 Comparative Example 1 is based on Example 1. The difference between Comparative Example 1 and Example 1 is that ZIF-8 (MOF with imidazole as ligand) is used instead of carboxylic acid MOFs in Comparative Example 1.

[0031] Comparative Example 2 Comparative Example 2 is based on Example 1. The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 did not add methyl phenolic resin in S3.

[0032] Performance testing Samples from Examples 1-4 and Comparative Examples 1-2 were taken and subjected to the following performance tests: (1) Initial discharge specific capacity and initial coulombic efficiency Using GB / T 31486-2015 as the testing reference, the initial discharge specific capacity and initial coulombic efficiency of the samples were tested. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1.

[0033] (2) 5C / 0.1C ratio Using GB / T 31484-2015 as the testing reference, the 5C / 0.1C ratio performance of the samples was tested. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.

[0034] (3) 0.5C / 2000 cycles capacity Using GB / T 31486-2015 as the testing reference, the capacity retention rate of the samples at 0.5C / 2000 cycles was tested. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1.

[0035] Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-2

[0036] As shown in Table 1, the carboxylic acid MOFs / graphene oxide (GO) / phenolic resin composite material prepared in this application, as a negative electrode material for lithium-ion batteries, has higher initial discharge specific capacity, better coulombic efficiency, rate performance and cycle stability compared with the comparative example.

[0037] As can be seen from Examples 1-4, the ratio of MOFs:GO:phenolic resin has a significant impact on performance. A ratio of 1:1:1 results in superior rate performance; while a ratio of 1:1:2 shows better capacity retention, reaching 96.5% after 2000 cycles. This is because increasing the proportion of phenolic resin enhances its supporting role, stabilizes the composite framework formed by MOFs and GO, reduces structural collapse and loss of active sites during cycling, thereby improving cycle stability. However, if the ratio is too high, excessive phenolic resin will partially cover the conductive surface of GO, increasing charge transport resistance and causing a slight decrease in rate performance. Furthermore, reducing the GO ratio (e.g., MOFs:GO = 1:0.5 in Example 2) weakens the continuity of the conductive network, reduces charge transport efficiency, and decreases rate performance; however, because the number of active sites is not significantly reduced, the initial discharge specific capacity remains at a high level.

[0038] Comparing Comparative Examples 1-2 with the Examples, it is evident that the material prepared using carboxylic acid MOFs through an in-situ composite process exhibits superior overall performance. Carboxylic acid MOFs can chemically anchor with phenolic resins, enhancing interfacial bonding and preventing component stripping during charge and discharge. The in-situ composite method helps construct a continuous conductive network and a stable framework structure, reducing interfacial side reactions, thereby simultaneously achieving high specific capacity, high coulombic efficiency, and long-term cycle stability. In contrast, Comparative Example 1, lacking chemical anchoring due to the use of non-carboxylic acid MOFs, and Comparative Example 2, failing to form a stable conductive network due to physical mixing, both resulted in significant performance degradation.

[0039] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A graphite anode material containing dicarboxylic acid MOFs, characterized in that: Includes the following steps: S1. Mix the organic ligand, zirconium salt and solvent, and heat to react to obtain the reactants; S2. After cooling the reactants, filter them, remove the filter residue, wash it, then filter and dry it to obtain carboxylic acid MOFs; S3. Disperse carboxylic acid MOFs and graphene oxide in anhydrous ethanol, add phenolic resin, and obtain a mixture; S4. Dry the mixture to remove the solvent, then heat it to cure, and obtain the pre-cured product; S5. High-temperature carbonization under inert gas conditions yields carbonized products; S6. The obtained carbonized product is soaked in hydrogen fluoride solution to remove inorganic impurities, then washed until neutral, and dried to obtain graphite anode material containing dicarboxylic acid. In step S1, the organic ligand contains at least two carboxylic acid groups.

2. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S1, the organic ligand is preferably 4,4'-stilbene dicarboxylic acid, and the zirconium salt is preferably zirconium tetrachloride.

3. The graphite anode material containing dicarboxylic acid MOFs according to claim 2, characterized in that: The mass ratio of 4,4'-stilbene dicarboxylic acid to zirconium tetrachloride is 1:(0.7-0.8).

4. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S1, the temperature for the reaction between the organic ligand and the zirconium salt is 110-130℃, and the reaction time is 22-24h.

5. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S2, the drying temperature of the filter residue after washing and filtration is 110-130℃, and the drying time is 6-12h.

6. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S3, the mass ratio of carboxylic acid MOFs, graphene oxide, phenolic resin and anhydrous ethanol is 1:(0.8-1.2):1:

20.

7. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S3, the phenolic resin is a first-order phenolic resin.

8. The graphite anode material containing dicarboxylic acid MOFs according to claim 1, characterized in that: In step S5, the high-temperature carbonization temperature is 880-920℃, and the carbonization time is 5-8h.

9. A graphite anode material containing dicarboxylic acid MOFs as described in any one of claims 1-8, characterized in that: The graphite anode material containing dicarboxylic acid MOFs is used in lithium-ion batteries.